2003
DOI: 10.1007/s00127-003-0618-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a model of caregiving for people with psychosis

Abstract: The findings provide some support for an interactive, stress-coping model of caregiving in psychosis. Effective coping in caregivers may improve with support from confidants. Carer distress may not change while caregiving continues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 20 publications
3
36
0
1
Order By: Relevance
“…A range of background factors may also shape adjustment to caregiving including carer, CR, and caregiving context variables. The few studies on mental health carers that have been guided by stress/coping theory have not closely linked their theoretical constructs with the original theory and/or have examined only relations between adjustment and one or two stress/coping components (e.g., Joyce et al, 2003). We could find no published longitudinal study that had examined all key components of the stress/coping framework in predicting variations in carer adjustment to mental health caregiving in both positive and negative adjustment domains.…”
Section: Stress and Coping Theorymentioning
confidence: 84%
“…A range of background factors may also shape adjustment to caregiving including carer, CR, and caregiving context variables. The few studies on mental health carers that have been guided by stress/coping theory have not closely linked their theoretical constructs with the original theory and/or have examined only relations between adjustment and one or two stress/coping components (e.g., Joyce et al, 2003). We could find no published longitudinal study that had examined all key components of the stress/coping framework in predicting variations in carer adjustment to mental health caregiving in both positive and negative adjustment domains.…”
Section: Stress and Coping Theorymentioning
confidence: 84%
“…Currently, no eating disorder model takes into account informal social support (such as friends and family members) as a predictor of burden or distress. However, research examining schizophrenia carers has shown that informal social support predicts a positive caregiving experience [42] and those who lack social support use more ineffective coping strategies and have a more negative appraisal of the caring situation [43]. Further, satisfaction with social support significantly predicts distress, positive affect and satisfaction with life in young carers [30].…”
Section: Discussionmentioning
confidence: 99%
“…4 Many other organizations provide excellent resources about mental health/illness, recovery, empowerment and advocacy although they are not focused on assisting family members specifically. These include Mental Health America (http://www.nmha.org, formerly the and Draine 1995; Noh and Turner 1987;Joyce et al 2003). These mediating conditions can include the individual's cognitive style, coping skills, and personality, plus other external stressors and resources (Kramer 1993).…”
Section: Family Members and Professional Helpmentioning
confidence: 97%